The legal framework for the future contract in the stock market - نافع, خالص امين; محمد, اياد جواد (Journal of Legal Sciences, 2021)
According to this contract, it is agreed to postpone the receipt and payment the price to a specific time to be agreed upon, which is in fact the settlement of the difference between the price of the contract on the day of the conclusion and its price on the settlement day.A future contract in this understand shall be a negotiable security in the organized markets, where the seller or the buyer shall replace the seller or the purchaser in their legal status with another person, regardless of the consent of the other party. The Iraqi legislator organized the future contract in many acts because of its importance.